"Armed with arms" an informational campaign using Web-based materials to promote Philippine martial arts - Lalic, Loewe Isabel F.; Austria, Romanlito (Quezon City College of Fine Arts, University of the Philippines Diliman, 2018)
Arnis (also known as eskrima or kali) is a Filipino martial art more popularly known for its stick fighting forms, but also shines through with its different focuses on weapon-based fighting with varied weaponry and unarmed fighting. The martial art is popular in newer foreign media like television, video games, and TV shows despite its lack of patronage locally, however the display of arnis is not obvious, as people only associate arnis with stick fighting. As a result, there are many shows and media that feature arnis, but only a few Filipinos know or can appreciate. Armed with arnis, a collaboration campaign with several local arnis groups and school-based arnis clubs, aims to teach basic arnis to be able to visually appreciate and identify the martial art, using a video game to demonstrate the technicalities and the weaponry used in the martial art and using its story to highlight historical events that had affected arnis' development over the years. The website is used to catalog and detail all of this information, and social mediais to be used to analyze FMA in existingmedia, for the audience to look back and appreciate the presence of arnis in current media.
Thesis (Bachelor of Fine Arts in Visual Communication)--University of the Philippines Diliman
Bibliography : leaves 102-104.
Keywords: Martial arts -- Philippines